Genetic heterogeneity of congenital hypertrophy of the retinal pigment epithelium (CHRPE) in families with familial adenomatous polyposis. - Hodgson, S V (1994)
One hundred and eighteen subjects with familial adenomatous polyposis (FAP) and 80 of their relatives who were at low risk (< 0.01) of carrying the FAP gene were scored by one of us (BJ) or by colleagues to assess the frequency of congenital hypertrophy of the retinal pigment epithelium (CHRPE). A CHRPE is defined as an "oval pigmented lesion surrounded by depigmented halo". Seventy five (63.6%) of the FAP cases and one (1.2%) of their relatives had at least one CHRPE. There was no systematic difference in the number of CHRPEs in the left and right eyes so all analyses are based on total number of CHRPEs and the findings were highly correlated (p = 0.001 for a test of no correlation). There was also no evidence of any age effect in total number of CHRPEs in affected subjects. In 26 families there was more than one subject affected with FAP. There was a significant common family effect with respect to CHRPE expression for total number of CHRPEs with an F statistic of 1.73 (p = 0.02 for a test of no family aggregation) indicating that family members are more similar to each other than to affected subjects from other families. This may indicate that specific mutations play a role in determining the number of CHRPEs. Nine affected subjects had intra-abdominal desmoids, and in these the frequency of each of the types of CHRPE was no higher (in fact, slightly lower) than the average for affected subjects without desmoids, but this difference was not significant (p > 0.3).